2011
DOI: 10.1021/jf104928r
|View full text |Cite
|
Sign up to set email alerts
|

Multielemental Fingerprinting as a Tool for Authentication of Organic Wheat, Barley, Faba Bean, and Potato

Abstract: The multielemental composition of organic and conventional winter wheat, spring barley, faba bean, and potato was analyzed with inductively coupled plasma-optical emission spectrometry (ICP-OES) and -mass spectrometry (ICP-MS). The crops were cultivated in two years at three geographically different field locations, each accommodating one conventional and two organic cropping systems. The conventional system produced the highest harvest yields for all crops except the nitrogen-fixing faba bean, whereas the dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 26 publications
(56 reference statements)
7
78
0
3
Order By: Relevance
“…The crops were grown in two successive years, 2007 and 2008 (years 1 and 2), at three different locations, Flakkebjerg (Fla), Jyndevad (Jyn), and Foulum (Fou), in Denmark. Further descriptions of field study design and of field and soil characteristics are given by Olesen et al 30 and Laursen et al 24 There was a total crop loss of fava beans in year 2 at Flakkebjerg due to a severe attack of aphids (Aphis fabae L.) and Fla-year 2 was excluded from the study, because it was not possible to compose the diets. Hence, the final number of experimental diets was reduced to 30.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The crops were grown in two successive years, 2007 and 2008 (years 1 and 2), at three different locations, Flakkebjerg (Fla), Jyndevad (Jyn), and Foulum (Fou), in Denmark. Further descriptions of field study design and of field and soil characteristics are given by Olesen et al 30 and Laursen et al 24 There was a total crop loss of fava beans in year 2 at Flakkebjerg due to a severe attack of aphids (Aphis fabae L.) and Fla-year 2 was excluded from the study, because it was not possible to compose the diets. Hence, the final number of experimental diets was reduced to 30.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…However, a study by Laursen et al 24 performed on crops from the same field experiment concluded that there were no systematic differences between organic and conventional crop content of essential plant nutrients (C, N, K, Mg, P, S, Ca, Fe, Mn, B, Zn, Cu, Mo, Ba, Sr, and Na), and mineral content was also affected by year and location. Using the data from the individual crops in the aforementioned study, it was also possible to calculate the mineral content of the diets, and NRC requirements for growing rats was met.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 98%
“…The limit of detection LOD was determined as 3 times the standard deviation of a minimum of 7 blanks. ICP-OES instrument settings were as described previously (Laursen et al, 2011).…”
Section: Multi-elemental Analysis Of Soils and Plantsmentioning
confidence: 99%
“…An elemental fingerprint analysis could serve as a descriptor of the geographical origin, and has the potential to enable authentication of organic crops (Kelly & Bateman, 2010). It was used, for example, in classification of winter wheat, spring barley, faba bean and potato (Laursen et al, 2011), honeys (Chua, Abdul-Rahaman, Sarmidi, & Aziz, 2012), virgin olive oils, pumpkin seed oils, wines and Chinese cabbage (Bandoniene, Zettl, Meisel, & Maneiko, 2013;Benincasa, Lewis, Perri, Sindona, & Tagarelli, 2007;Bong et al, 2012;Geana et al, 2013), onion cultivars based on mineral content (Chope & Terry, 2009;Galdón, González, Rodríguez, & Romero, 2008), and fruit and vegetables (Patras et al, 2011).…”
Section: Introductionmentioning
confidence: 99%